Reducing the quantity of students who have misconceptions about archimedes' law material using the Children Learning in Science (CLIS) model - Murdani, Eka; Kumala, Devi; Sumarli, Sumarli (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
This research aims to determine the decrease in the quantity of students who have misconceptions about Archimedes' law material after the CLIS learning model has been implemented, determine student responses to the CLIS learning model that has been implemented, and determine the implementation of learning activities using the CLIS model. The research was carried out using quantitative methods. The population in this research was all students of class XI IPA MAN 1 Singkawang. The data in the research was obtained by giving sheets to the students. The instruments used were a TTT sheet consisting of 10 questions, a student response sheet with 9 questions, an observation sheet on the implementation of the CLIS learning model. Based on the results of the analysis of students' misconceptions, the highest decrease was in the concept "Objects sink in water because objects are heavier than water" namely 64.2% in the medium category. Student response to the CLIS learning model was 85% in the positive category. The implementation of the CLIS learning model is 100% with all activities carried out in the category. Therefore, it can be concluded that implementing CLIS can reduce the quantity of students who have misconceptions.